The 3 T’s (Titan, Trailblazer, and Trustworthy) of Ed Latessa - Taxman, Faye S. (Victims & offenders, 2021)
The words that typify Ed Latessa are titan, trailblazer, and trustworthy. His career has been driven by a desire to change American corrections to intertwine research into routine practices. Ed’s work embraces the principles of evidence-based practices and treatments. His devotion to these principles, even in a political era that embraced mass incarceration policies and practices, has been transformative. Being a titan, Ed has led the charge to change the field by widely disseminating information about evidence-based practices and treatments and working directly with all agencies regardless of government level to promote research findings into practice. As a trailblazer, Ed has been at the forefront of the evidence-based corrections and paved the way for its implementation. And, Ed, being the honest agent, has used research findings to enlighten the field, even when the field was going in a different direction. Ed has helped the field learn how to integrate research findings into effective practices, including giving attention to rehabilitation. Ed is known for his honesty and willingness to use research findings to make his points. This essay outlines how Ed’s passion, perseverance, and transformative leadership style has guided the field with ease and commitment.